ChemInform Abstract: Design of Supported Organocatalysts from Carboxylic Acids for the Mannich‐Type Synthesis of β‐amino Carbonyl Compounds. Issue 17 (April 2016) - Sarma, Parishmita; Saikia, Susmita; Borah, Ruli
Abstract: β‐Amino carbonyl compounds (IV) are selectively synthesized via Mannich‐type reactions using silica‐supported trifluoroacetic acid as highly efficient reusable catalyst.